2010
DOI: 10.1097/tp.0b013e3181c518cc
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Avoidance or Withdrawal After Renal Transplantation Increases the Risk of Acute Rejection but Decreases Cardiovascular Risk. A Meta-Analysis

Abstract: Despite an increase in the risk of AR with SAW protocols, there is only a small effect on graft function with no measurable effect on graft or patient survival. There are significant benefits in cardiovascular risk profiles after SAW. SAW protocols would seem justified with current immunosuppressive protocols in low-risk recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(186 citation statements)
references
References 85 publications
12
166
3
5
Order By: Relevance
“…Older randomized trials demonstrated improvement in all of these parameters with implementation of steroid withdrawal or steroid-free immunosuppression (28). A recent meta-analyses of 34 randomized trials of steroid-free immunosuppression concluded that elimination of steroids was associated with improvements in hypertension, hyperlipidemia, and the incidence of new-onset diabetes after transplantation (29). The last two reports are flawed by their inclusion of older trials in which immunosuppression was dominated by the use of cyclosporine and relatively high dosages of maintenance corticosteroids.…”
Section: Role Of Immunosuppressionmentioning
confidence: 99%
“…Older randomized trials demonstrated improvement in all of these parameters with implementation of steroid withdrawal or steroid-free immunosuppression (28). A recent meta-analyses of 34 randomized trials of steroid-free immunosuppression concluded that elimination of steroids was associated with improvements in hypertension, hyperlipidemia, and the incidence of new-onset diabetes after transplantation (29). The last two reports are flawed by their inclusion of older trials in which immunosuppression was dominated by the use of cyclosporine and relatively high dosages of maintenance corticosteroids.…”
Section: Role Of Immunosuppressionmentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials of steroid withdrawal have demonstrated similar transplant outcomes despite an increased risk for acute rejection with early steroid withdrawal when compared to steroid maintenance. [8][9][10] A registry analysis by Luan and associates showed a reduced risk for graft failure and patient death at 1 and at 4 years in kidney transplant recipients continued on a steroid-free regimen. 11 The 5-year prospective randomized trial by Woodle and associates demonstrated reductions in weight gain, new onset of type 2 diabetes mellitus after transplant, and hypertriglyceridemia in kidney transplant recipients randomized to early steroid withdrawal following antibody induction and calcineurin inhibitor and mycophenolate mofetil maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…29 ). Also single-center studies have demonstrated that oral prednisolone dose reduction to 5 mg daily significantly improves glucose tolerance during the first year after transplantation 30 while a 0.01 mg/kg/day increase in prednisolone dose is associated with a 5% (ref.…”
Section: Glucocorticoidsmentioning
confidence: 99%